Plucked Human Hair Shafts and Biomolecular Medical Research. (31st October 2013) - Schembri, Kevin; Scerri, Christian; Ayers, Duncan
Abstract : The hair follicle is a skin integument at the boundary between an organism and its immediate environment. The biological role of the human hair follicle has lost some of its ancestral importance. However, an indepth investigation of this miniorgan reveals hidden complexity with huge research potential. An essential consideration when dealing with human research is the awareness of potential harm and thus the absolute need not to harm—a rule aptly qualified by the Latin term "primum non nocere" (first do no harm). The plucked hair shaft offers such advantages. The use of stem cells found in hair follicles cells is gaining momentum in the field of regenerative medicine. Furthermore, current diagnostic and clinical applications of plucked hair follicles include their use as autologous and/or three-dimensional epidermal equivalents, together with their utilization as surrogate tissue in pharmacokinetic and pharmacodynamics studies. Consequently, the use of noninvasive diagnostic procedures on hair follicle shafts, posing as a surrogate molecular model for internal organs in the individual patient for a spectrum of human disease conditions, can possibly become a reality in the near future.